Development of an intraoral device for social inclusion of a physically disabled patient. (18th November 2015) - de Mesquita‐Guimarães, Késsia Suênia Fidelis; Ferreira, Danielly Cunha Araújo; da Silva, Raquel Assed Bezerra; Díaz‐Serrano, Kranya Victoria; de Queiroz, Alexandra Mussolino; Mantovani, Carolina Paes Torres; De Rossi, Andiara
ABSTRACT: The aim of this study is to describe the use of an intraoral assistive technology for a patient with idiopathic generalized muscular dystonia, presenting temporomandibular disorder and severe anterior tooth mobility and diastema. A multidisciplinary team developed an intraoral device to provide typing and painting functions, and promote relaxation of masticatory muscles without compromising the teeth and supporting tissue structures. The occlusal splint associated with the device promoted muscle relaxation and relief of the signs and symptoms of temporomandibular dysfunction, in this case with generalized muscle dystonia, allowing typing and painting with her mouth without causing tooth mobility or occlusal alteration. This intraoral device has low cost, easy adaptation and was efficient in TMD symptoms. Furthermore, the patient returned to her rehabilitation allowing performance of her duties without compromising dental structures, facilitating the social and the digital inclusion.